Mediating the Otherworld in Polish Folklore A Cognitive Linguistic Perspective - Masłowska, Ewa (Polish Studies - Transdisciplinary Perspectives, 2020)
This book analyses the ways of conceptualising and interpreting the interaction between physical and metaphysical worlds in Polish folklore. A linguistic and anthropological analysis offered in this study focuses primarily on myth, ritual and symbol as reflected in language (dialect lexis, phraseology, speech acts). Employing the methodology and analytical tools of cognitive linguistics (preconceptual image schemas, cognitive scene, profiling of concepts, development of cognitive paths), the author reconstructs mental patterns at the heart of mythical thinking, linguistic actions and symbolic meanings, which reflect universal conceptual schemas and may serve as models for intercultural studies.